Risiko Aplikasi Dana dan Tingkat Kepuasan Konsumen di Provinsi Jambi Dalam Perspektif Islam: Studi Kasus Generasi Z - Dean Amri, Ary; Hesti Imraatun Nadziroh; Asroful Anam; Novita Sari; Nadhilah Putri Riani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the risks of use, the level of consumer satisfaction, as well as the general and Islamic legal basis for generation z in Jambi province. This research is a Mixed Research (Quantitative-Qualitative) using a Descriptive Approach. The test method used is the Reliability Test and Validity Test with the SPSS 26 Analysis Tool, and the test uses a Likert scale. The results showed that 243 respondents were declared neutral on the Likert Scale Analysis Test. Meanwhile, the reliability and validity test shows that research on the risk of application of funds and the level of consumer satisfaction in Jambi Province from an Islamic perspective (Case Study of Generation Z) is reliable or consistent.